If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2 = y + 11 Reorder the terms: 2 + 4y = y + 11 Reorder the terms: 2 + 4y = 11 + y Solving 2 + 4y = 11 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + 4y + -1y = 11 + y + -1y Combine like terms: 4y + -1y = 3y 2 + 3y = 11 + y + -1y Combine like terms: y + -1y = 0 2 + 3y = 11 + 0 2 + 3y = 11 Add '-2' to each side of the equation. 2 + -2 + 3y = 11 + -2 Combine like terms: 2 + -2 = 0 0 + 3y = 11 + -2 3y = 11 + -2 Combine like terms: 11 + -2 = 9 3y = 9 Divide each side by '3'. y = 3 Simplifying y = 3
| p-1=5p+3p-9 | | 4z+3=6z-5 | | 9.7y+7.53=-54.55 | | 37x-15+44x-29=180 | | 4+x=2(x-5) | | 4(x+1010)=3(x-10101) | | 44-x=11 | | n+3.7=9.8 | | 2-5[x+3(x+7)]= | | 7x-31=-25 | | 8.5t=83.30 | | 4x-0=1 | | -23682-6k=6+18k | | 6x(x-9)=13x^2-55x | | 10x+7=-x-15 | | 5x=234 | | 8z=9z-3 | | 7+3t-1=8t+24-2t | | 2[4-9x]=9x+7 | | -143=3(-6b-1)+4 | | 6(5y-8)-(7y+4)= | | 9x^2+13=247 | | -4(1-5v)=-144 | | 7+5[1+2(2x+5)]=6(x+7) | | P-16=13-6p | | 4c+1-c=19 | | (x+5)(x-2)=35 | | 8b-5b-7=23 | | 8y+4y=144 | | 2.5[x+3(x+7)]= | | 6x+8y=-11 | | (3a)+(2a-25)=180 |